THE EFFECT OF THE AUDIO-VISUAL ASSISTED TALKING STICK METHOD ON ARABIC SPEAKING SKILL: PENGARUH METODE TALKING STICK BERBANTUAN AUDIO - VISUAL TERHADAP MAHARAH KALAM - Nurriyatul Masrifah; Ahmad Sholihuddin; Putri Kholida Faiqoh (Muaddib: Journal of Arabic Language and Literature, 2024)
This study aims to determine the effect of the application of audio-visual-assisted talking stick method in developing students' maharah kalam. This research uses a quantitative approach with a quasi-experimental method. The research instruments included observation, tests and documentation, with data analysis using Chi-Quadrat normality test, homogeneity test and independent sample T- Test. The results showed that the average value of the control class pretest was 55.2 and increased to 77.2 in the post-test. Meanwhile, the average value of the experimental class pretest was 54.6, which then increased to 81.4 in the post-test. The t-count value of 3.695 with a significance value of 0.001 shows that t> t table, so H0 is rejected and Hais accepted. Thus, there is a significant difference between the experimental group and the control group. The conclusion of this study is that the Talking Stick learning method assisted by audio-visual media has a positive and significant influence on the development of maharah kalam of seventh grade students at MTsN 2 Blitar City. The impact of applying this method includes increased student engagement in learning, strengthened active communication skills, and increased student confidence in using Arabic.